Pengaruh Perceived Price, Digital Marketing, dan Positive Word of Mouth Terhadap Keputusan Pembelian Produk Herborist di Stuffbyms Kota Semarang - Saccidananda Octyangelin Santosa; Ali Maskur (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
The purpose of this study is to analyze how consumer behavior at the Stuffbyms skincare store in Semarang City is influenced by Perceived Price, Digital Marketing, and Positive Word of Mouth. The sample in this study were social media followers of Herborist at Stuffbyms skincare shop in Semarang City using purposive sampling technique and distributing questionnaires via social media. Some tests were carried out using spss version 26. This matter is included in the validity, reliability, F test, coefficient of determination (R2), and t test for data analysis. The results of the study according to statistics show that Perceived Price has a significance level of 0.003, Digital Marketing has a significance level of 0.001, and Positive Word of Mouth has a significance level of 0.005. All of these factors as a whole have a positive and significant effect on purchasing decisions for Herborist products.